Antimicrobial Prescribing Rates Comparing On-Site Visits with Two Types of Virtual Care Visits Across a Large Integrated Healthcare System. (4th October 2017) - Schmidt, Monica; Spencer, Melanie D; Davidson, Lisa E
Abstract: Background: In 2014, Carolinas Healthcare System (CHS) implemented virtual visits and Electronic visits (eVisits) as an alternative to on-site visits to provide novel and convenient ways for patients to access care for non-emergent conditions. With virtual visits, patients have a face-to-face consultation with a provider by logging onto any device equipped with a camera. eVisits offer a lower tech alternative that allow patients to email their health concerns through a series of health-related questions. Providers respond via email with recommendations. No face-to-face interaction is included with eVisits. This study aimed to compare prescribing rates across these care delivery options. Methods: We identified 2, 478 virtual visits, 269 eVisits and 655, 329 on-site visits between Jan 2014 to Feb 2017 where there was any diagnosis of bronchitis, sinusitis, non-suppurative otitis media and upper respiratory infection. Antimicrobial prescribing rates were standardized to per 100 visits (reported as a %) for each indication. Prescribing rates are reported for each visit type and indication. Chi square tests were used to compare rates across the visit types. Results: Across all visit types and indications, on-site visits had the highest rate of antimicrobial prescribing and eVisits the lowest (onsite: 55.0; virtual: 51.3; eVisit 33.8; P < 0.001). Sinusitis was the most frequent indication for which an antimicrobial was prescribed, with on-site visits (86.6%), virtual (72.9%) and eVisits(57.8%) showing significantly different rates ( P < 0.001). For upper respiratory infections, where an antimicrobial is not indicated, 34.5% of on-site, 11.0% of virtual and 2.0% of eVisits received an antimicrobial prescription ( P < 0.001). Conclusion: The mechanism of care delivery significantly impacts whether or not an antimicrobial is prescribed for specific diagnoses where a prescription may not be indicated. eVisits had the lowest rates of inappropriate prescribing for URI while on-site care showed significantly higher antimicrobial prescriptions. Further investigation is needed into the underlying causes of prescribing rate variances and how these care delivery options may affect efforts to reduce inappropriate utilization of antimicrobials. Disclosures: All authors: No reported disclosures.